Vitamin D for Recovery of COVID-19 in Patients With Chronic Kidney Disease - Chiang, Wen-Fang; Hsiao, Po-Jen; Chan, Jenq-Shyong (Frontiers in Nutrition, 2022)
The severity of coronavirus disease 2019 (COVID-19) is determined not only by viral damage to cells but also by the immune reaction in the host. In addition to therapeutic interventions that target the viral infection, immunoregulation may be helpful in the management of COVID-19. Vitamin D exerts effects on both innate and adaptive immunity and subsequently modulates immune responses to bacteria and viruses. Patients with chronic kidney disease (CKD) frequently have vitamin D deficiency and increased susceptibility to infection, suggesting a potential role of vitamin D in this vulnerable population. In this paper, we review the alterations of the immune system, the risk of COVID-19 infections and mechanisms of vitamin D action in the pathogenesis of COVID-19 in CKD patients. Previous studies have shown that vitamin D deficiency can affect the outcomes of COVID-19. Supplementing vitamin D during treatment may be protective against COVID-19. Future studies, including randomized control trials, are warranted to determine the effect of vitamin D supplementation on the recovery from COVID-19 in CKD patients.